(untitled) (Bangladesh Journal of Microbiology, 2010)
To assess the bacteriological quality 768 drinking water samples were collected from different locations in Khairpur City, Sindh, Pakistan over a period of two years from January 2006 to December 2007. The study reveals that out of 768 drinking water samples 567 (73.83%) samples were found to be contaminated with total coliform among them 85 (11.06%) found in the January-March period, 182 (23.70%) in April-June period, 188 (24.47%) in July-September, 112 (14.58%) in October-December period. Faecal coliform was found in 351 (45.70%) water sample, in which 49 (15.80%) occurred during January-March, 137 (17.83%) during April-June, 136 (17.71%) during July-September and 69 (8.98%) during September-December. It can be concluded from the results of the present study that bacteriological quality of two-third drinking water in Khairpur City is not safe as the water is the potential source of diarrhoeal disease agents. Keywords: Drinking water; Khairpur City; Faecal pollution; Diarrhoea DOI: http://dx.doi.org/10.3329/bjm.v25i1.4862 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 69-72